Identifikasi Kesulitan Menentukan Media Pembelajaran pada Mahasiswa PGSD - Muhammad Daffa Rizky Alviansyah; Awalliyah, Rinda Ayu Nur; Na'imah, Laila Janatin; Putri, Faradila Arfina; Alam, Muhammad Bahrul (Nur Science Institute, 2022)
Background: Compiled this research with the aim of describing and explaining the difficulties of students, especially UMS PGSD students in preparing learning media Method: This research uses a qualitative approach with a case study method. Research using the case study method tries to discuss as deeply as possible the subject you want to research, then describe it in more detail, by understanding as deeply as possible an individual, a group, or a phenomenon. This research is intended to provide a complete and in-depth view of the subject to be researched. Result: The results show that the learning media prepared by students have problems encountered. In fact, in the preparation of instructional media students are sometimes asked to compile in groups so that problems or obstacles faced by these students arise. This causes learning media to know the obstacles and how to overcome them. Implication: The implications of this study are learning by media in Indonesia should enrich the teachers' knowledge and insight related to learning medias. Novelty: The present study revealed the implementation of learning media and constraints in education.